Pendampingan Perencanaan Implementasi dan Evaluasi Program Kesehatan Bebas Anemia Remaja Berkarya - Angelina, Devita; Hadyandiono, Chrisna Nur (Universitas Nurul Jadid, 2024)
Health program planning was carried out to develop a mature and well-organized health plan to achieve predetermined health goals within a certain timeframe. Based on a systems approach, a survey through questionnaires, and determining priority problems through USG (Urgency, Seriousness, and Growth), the result obtained was that 84% of teenage girls at SMPN 41 Surabaya did not adhere to consuming Iron Deficiency Anemia tablets (TTD). Following that, a root cause analysis of the issue was conducted utilizing a fishbone diagram, and the main cause related to this problem was found, which was the absence of a routine schedule for TTD assistance. Hence, several alternative solutions were given priority based on the MEER method (Methodology, Effectiveness, Efficiency, and Relevance).. From this method, it was concluded that the selected solution that could be implemented was the provision of the